Utilization of Mosquito Nets and Malaria Related Under-Five Mortality in Abia State, Nigeria - Kingsley, Imo, Chukwuechefulam; Uche Charlie, Isiugo-Abanihe (European Scientific Journal, ESJ, 2016)
In spite of huge global investments in the production and distribution of mosquito nets to protect people from malaria; it has continued to militate against the reduction of mortality in Nigeria. The study, therefore, examined the nexus between utilization of mosquito nets and malaria related under-five health outcome. Two local government areas were randomly selected from each of the three senatorial districts, and stratified along urban and rural communities. Purposive sampling technique was used to select 609 mothers within childbearing age and who had under-five children across the communities. Descriptive statistics, Chi-square tests and logistic regression at p<0.05, and thematic content analysis were used for data analyses. The respondentsâ€™ age was 32.6Â±5.8 years, 84.6% were married/living together, 55.0% had secondary education, while 42.7% were in paid/civil service jobs. Under-five mortality was 19.3% higher amongst rural than urban dwellers. Ownership of mosquito nets (treated or untreated) varied by place of residence with 60.1% and 39.9% for urban and rural areas respectively. About 62% of the dead under-five children never slept under mosquito nets. The likelihood of under-five mortality significantly increased by nonownership of mosquito nets (Odds-Ratio (OR): 2.476) and reduced by number of mosquito nets (OR: 0.278). Wrong methods adopted by mothers in using mosquito nets, was deduced as a contributory factor causing underfive mortality for home with fewer nets. Information on the proper use of the mosquito nets would help achieve the goal of universal access for the atrisk populations of children under age five and pregnant women.